The origin of relic cryogenic mounds at East Walton and Thompson Common, Norfolk, England. Issue 4 (October 2015) - Clay, P.
Abstract: Contemporary pingo and lithalsa mounds are features which develop exclusively within cold climate environments in areas of continuous and discontinuous permafrost. The presence of pingo and lithalsa remnants as rampart enclosed ponds has been documented across temperate areas of the Northern Hemisphere and has been used to establish the extent of former permafrost. Two sites thought to be remnants of hydraulic pingo forms were investigated at East Walton and Thompson Common(s) in order to establish a precise origin. Through Ground Penetrating Radar and Electrical Resistivity Tomography the structure of ramparts and hollows has been investigated and interpreted. Linking this with physical and ground invasive techniques and a consideration of the hydrogeological setting it was apparent that the two sites had different origins. The topography, geology and hydrogeology of the East Walton area are a stereotypical setting for the development of hydraulic pingos. In contrast, the development of features within the Lowestoft Till and weathered Chalk Formations at Thompson Common implies that forms resulted from the heave of material through segregation ice lens growth. This has led to the creation of a model at East Walton which documents the development of remnant pingo ramparts and the strata which result. It is proposed that this model can be used in the study of similar landforms.